Pengembangan Media Video Pembelajaran Berbasis Canva pada Pembelajaran Pendidikan Pancasila Materi Bahasa Indonesia Sebagai Bahasa Persatuan di Kelas IV Sekolah Dasar - Atika, Diadara; Masniladevi, Masniladevi; Anita, Yesi; Fitria, Yanti (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to develop Canva-based video learning media for learning. This research is a research development study or Research and Development (R&D) using the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. After analyzing the facilities and infrastructure, curriculum, needs, and materials, the researcher designed Canva-based video learning media, which was then validated by material experts, language experts, and media experts. The results showed that the Canva-based learning video media is very valid with a score of 96% by material experts, 98% by language experts, and 91% by media experts, with an average validity of 95%. The practicality test results showed that the learning video media is very practical with a score of 96% by teachers and 93% by students at SD N 02 Pasaman, as well as 93% by teachers and 92% by students at SD N 09 Pasaman. The effectiveness test results showed that the learning video media is very effective to use at SDN 02 Pasaman with an N-Gain score of 86% (high) and at SDN 09 Pasaman with an N-Gain score of 80% (high). Therefore, the Canva-based learning video media is stated to be valid, practical, and effective for use in Pancasila education learning in the fourth-grade elementary school.